Mesoscale Soil Moisture Patterns Revealed Using a Sparse In Situ Network and Regression Kriging. Issue 6 (12th June 2019) - Ochsner, Tyson E.; Linde, Evan; Haffner, Matthew; Dong, Jingnuo
Abstract: Soil moisture spatial patterns with length scales of 1‐100 km influence hydrological, ecological, and agricultural processes, but the footprint or support volume of existing monitoring systems, for example, satellite‐based radiometers and sparse in situ monitoring networks, is often either too large or too small to effectively observe these mesoscale patterns. This measurement scale gap hinders our understanding of soil water processes and complicates calibration and validation of hydrologic models and soil moisture satellites. One possible solution is to utilize geostatistical techniques that have proven effective for mapping static patterns in soil properties. The objective of this study was to determine how effectively dynamic, mesoscale soil moisture patterns can be mapped by applying regression kriging to the data from a sparse, large‐scale in situ network. The fully automated system developed here uses several data sets: daily soil moisture measurements from the Oklahoma Mesonet, sand content estimates from the Natural Resource Conservation Service Soil Survey Geographic Database, and an antecedent precipitation index computed from National Weather Service multisensor precipitation estimates. A multiple linear regression model is fitted daily to the observed data, and the residuals of that model are used in a semivariogram estimation and kriging routine to produce daily statewide maps of soil moisture at 5‐, 25‐, and 60‐cm depths at 800‐m resolution. During over 3 years of operation, this mapping system has revealed complex, dynamic, and depth‐specific mesoscale patterns, reflecting the shifting influences of both soil texture and precipitation, with a mean absolute error of ≤0.0576 cm 3 /cm 3 across all three depths. Key Points: The scale gap between satellite footprints and in situ measurements obscures mesoscale soil moisture patterns Fully automated regression kriging routine developed here produces daily 800‐m soil moisture maps for Oklahoma at 5‐, 25‐, and 60‐cm depths This mapping system reveals dynamic mesoscale soil moisture patterns, reflecting the shifting influences of soil texture and precipitation